Eksplorasi Konsep "النفس" dalam Al-Quran (penelitian semantik kata فسٌٕا dalam bentuk isim mufrodnya pada Al-Quran): penelitian makna leksikal dan kontekstual - Jamaludin, Agus; Erihadiana, Mohamad (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
This research investigates the meanings and significance of the word "النفس" in the Quran through a comprehensive lexical and contextual approach. Within the Quranic context, this word is employed with various nuances of meaning, posing challenges to accurate comprehension. The research methodology encompasses a literature review, lexical analysis, contextual analysis, the study of interpretations (tafsir), and the formulation of conclusions. This study holds significant relevance in deepening the understanding of the Quran, enriching Quran translations, and contributing to the fields of religious studies and Islamic studies. The meaning of the word "النفس" in the Quran may vary depending on the context of the verses in which it is used. In some verses, it refers to the life or soul of a human being, while in others, its meaning pertains to the nature of humans, particularly the inclination towards wrongdoing, or it denotes a guilty conscience. This meaning is essential for comprehending the messages and teachings of the Quran, as well as the importance of safeguarding the soul and human behavior in accordance with the principles of the Islamic faith.